THE RIGHT MOMENT OR THE AWAKENING OF THE EDITORIALS' CHANGES IN FRENCH LITERATURE IN THE EIGHTIES AS SEEN BY LITERARY MAGAZINES - Almeida, José Domingues de (2012)
The eighties represent a turning point and an important change in the narrative features of French literature. In a way, they start the literary contemporarity as we know it from a critical point of view. They show some hesitations of critique about the emerging literature.